Monoclonal human IgGs capable of neutralizing elapid neurotoxins in vivo - Pus, Urska (2019)
The two elapids, the black mamba (Dendroaspis polylepis) and the monocled cobra (Naja kaouthia) are notorious for their bite, which each year causes a substantial share of the severe envenomings that occur in sub-Saharan Africa and Southeast Asia, respectively. Through a combined toxicovenomics and the phage display selection approach, monoclonal fully human IgGs were discovered and assessed for their ability to neutralize medically relevant toxins from the aforementioned snakes in vivo. The discovered monoclonal human IgGs were expressed in mammalian Expi-293 cells and tested in CD-1 mice using two different routes of administration. Initially, IgGs were incubated for 30 min at 37°C together with their target toxins in different molar ratios (mol toxin: mol IgG of 1:3 to 1:8) and then administered either intracerebroventricularly (i.c.v.) (dendrotoxins) using a toxin dose of 0.5 μg or intravenously (i.v.) (α-cobratoxin) using a toxin dose of 4 μg to evaluate the neutralization potential of the IgGs. The survival of mice administered with lethal doses of elapid toxins was substantially prolonged by the monoclonal human IgGs. Hence, we report the discovery of monoclonal fully human IgGs that are able to neutralize snake toxins in vivo. Additionally, one of the tested human IgGs was able to prolong survival both against its cognate toxin (α-cobratoxin) and against whole venom from N. kaouthia. This demonstrates the applicability of the Toxicity Score for identifying medically relevant toxins in a venom and that α-cobratoxin is one of the key toxic components of N. kaouthia venom.